(untitled) (Indian Journal of Child Health, 2019)
Background: Prolonged rupture of membrane (PROM) is an important risk factor for early-onset neonatal sepsis (EONS) and preterm births. Objective: The objective of this study was to determine the incidence of EONS in relation to PROM of more than 18 h. Materials and Methods: The study was conducted in a medical college in South India. All the neonates born to mothers with a history of PROM for >18 h were included in this study. Sepsis was diagnosed by clinical signs and symptoms and positive blood culture. Results: A total of 200 neonates were included in the study. Among these, confirmed sepsis was diagnosed in 18% (29); statistically, there was no significant difference (p>0.05). A high incidence of sepsis was found in neonates born by normal vaginal (68.5%) delivery. There was no significant difference between incidence of sepsis and duration of PROM; the range was 18–72 h. Conclusion: Sepsis was diagnosed to be less in neonates born to mothers who had prenatal antibiotics.